Poster 122: Characterizing Health Events and Return to Sport in Elite Collegiate Swimmers. Issue 7 (30th July 2022) - Greig, Danielle; Schroeder, Grant; Kremen, Thomas; Trikha, Rishi
Objectives: Competitive swimming is a common activity among pediatric, collegiate and masters-level athletic populations. It is also one of the most prestigious sports in the United States with regard to medal-winning at international competitions, however, epidemiologic studies describing the incidence of health events and outcomes in an elite swimming population are lacking. This study aimed to identify the most common injuries and illnesses among elite swimmers as well as how these injuries and illnesses affect return to sport following injury. Methods: This retrospective study utilized a de-identified injury and illness database of NCAA Division I collegiate swimmers in the United States from 2016 to 2020. Analysis included musculoskeletal injuries stratified by body location, as well as non-musculoskeletal injuries and illnesses. Relative risk (RR) was used to compare the percentage of athletes affected between males and females, with statistical significance being defined by a relative risk 95% confidence interval (CI) not including 1 ( P < 0.05). Results: 641 collegiate swimmers (301 male, 340 female) who were on a collegiate roster from 2016-2020 were included for analysis. A total of 1030 health events among 277 females and 173 males were analyzed. Of these 1030 health events, 635 (61.7%) occurred in females and 395 (38.3%) in males. Females were at a significantly higher risk of suffering musculoskeletal injury than males (RR = 1.5, 95% CI: 1.22 – 1.83). Females were also at a significantly higher risk of suffering a non-musculoskeletal injury/illness than males (RR = 1.32, 95% CI: 1.04 – 1.68). The most common of the 540 musculoskeletal injuries reported involved the shoulder (126, 23.3%), spine (95, 17.6%), foot/ankle/lower leg (81, 15.0%), knee/thigh injuries (67, 12.4%) and hand/wrist/forearm (52, 9.6%). The most common of the 490 non-musculoskeletal health events were respiratory tract infections (119, 24.3%), unspecified medical illness (93, 19.0%), concussions (58, 11.8%), ear infections (25, 5.1%) and gastrointestinal illnesses (24, 4.9%). Of the 58 documented concussions, 22 (37.9%) were season-ending. Fourteen of those 22 (63.6%) concussions were career-ending. Females had significantly higher rates of concussions (RR = 2.11, 95% CI: 1.13 – 3.96), 9.1% vs. 4.3%. Five out of 67 knee injuries (7.5%) were career-ending whereas only 1 out of 126 (0.8%) shoulder injuries was career-ending. Conclusions: This retrospective study identifies the most common injuries and illnesses as well as the most common season-ending or career-ending injuries and illnesses among elite collegiate swimmers. Awareness of the incidence and outcome of injuries and illnesses that affect competitive swimmers may allow for more targeted analysis and injury prevention strategies. Table 1. Musculoskeletal Injuries by Body Part for Collegiate Swimmers from 2016-2020 Table 2. Return to Sport Data for Most Common Diagnoses for Musculoskeletal Injuries and Non-Musculoskeletal Illnesses in Collegiate Swimmers from 2016-2020 Table 3. Return to Sport Data for Most Common Musculoskeletal Injuries in Collegiate Swimmers from 2016-2020 Stratified by Body Part